2016
DOI: 10.1007/s10103-016-2063-z
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Erbium:Yttrium aluminum garnet PIPS technique in comparison to different chemical solutions in removing the endodontic smear layer—an in vitro profilometric study

Abstract: This study evaluated the degree of endodontic smear layer removal using the Er:YAG PIPS technique (2.94 μm) in comparison with different irrigants. Sixty-four single-rooted teeth were endodontically prepared up to size #40 and were divided into 8 groups (a-h) (n = 8). Groups a, b, c, and d were irrigated with (3 % NaOCl + 20 % EDTA), (0.9 % NaCl), (3 % NaOCl), and (20 % EDTA), respectively. Groups e, f, g, and h were treated with (3 % NaOCl + 20 % EDTA + PIPS), (0.9 % NaCl + PIPS), (3 % NaOCl + PIPS), and (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Recently, photon‐initiated photoacoustic streaming (PIPS) with Er:YAG laser at low pulse energy (20 mJ) and short pulse duration (50 μs) was introduced in root canal irrigation (Balic et al, ; DiVito, Peters, & Olivi, ). The technology is based on the mechanism of bubble cavitation involving strong shockwaves due to collapse of bubbles in a fluid and is effective in removing the smear layer from the surrounding walls (Nasher, Franzen, & Gutknecht, ). Studies evaluating the efficacy of PIPS in endodontic treatment revealed that it is a potential technique for elimination of the smear layer and dentinal debris (Passalidou, Calberson, De Bruyne, De Moor, & Meire, ; Verstraeten, Jacquet, De Moor, & Meire, ); however, those authors did not perform systematic comparison of antimicrobial efficacy among irrigation solutions in routine use combined with PIPS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, photon‐initiated photoacoustic streaming (PIPS) with Er:YAG laser at low pulse energy (20 mJ) and short pulse duration (50 μs) was introduced in root canal irrigation (Balic et al, ; DiVito, Peters, & Olivi, ). The technology is based on the mechanism of bubble cavitation involving strong shockwaves due to collapse of bubbles in a fluid and is effective in removing the smear layer from the surrounding walls (Nasher, Franzen, & Gutknecht, ). Studies evaluating the efficacy of PIPS in endodontic treatment revealed that it is a potential technique for elimination of the smear layer and dentinal debris (Passalidou, Calberson, De Bruyne, De Moor, & Meire, ; Verstraeten, Jacquet, De Moor, & Meire, ); however, those authors did not perform systematic comparison of antimicrobial efficacy among irrigation solutions in routine use combined with PIPS.…”
Section: Introductionmentioning
confidence: 99%
“…Visuril et al reported good resin binding to dental tissues in laser treated samples, and that application of an Er: YAG laser to dentin yielded greater tensile strength than roughening [ 28 ]. Nasher et al found no smear layer in root canals prepared using an Er: YAG laser, together with opening of dentin tubules and increased tensile strength [ 29 ]. Akyüz et al also reported high tensile strength in samples activated using PIPS laser tips [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…54 The remaining studies showed no superiority of the Er:YAG laser in removing smear layers from root canals versus other techniques including the EndoActivator, 55,56 EndoVac, 26,56,57 LAI (Nd:YAG, Er,Cr:YSGG), 58 and CSI. 26,43,59 Despite this, three studies still found that PIPS was better than CSI. 55,57,58 The rest only tested PIPS or LAI and did not compare them with other techniques (Table 3).…”
Section: Debris Removalmentioning
confidence: 99%